Bacteraemia in severely malnourished children in an HIV-endemic setting - Babirekere-Iriso, Esther; Musoke, Philippa; Kekitiinwa, Adeodata (Annals of tropical paediatrics, 2006)
Background: HIV infection predisposes children with malnutrition to recurrent bacterial infections and a high risk of bacteraemia. Methods: A cross-sectional descriptive study to determine the prevalence, causative organisms, antibiotic sensitivity and factors associated with bacteraemia in malnourished children was undertaken at Mulago Hospital, Kampala. The prevalence of HIV infection was also determined. A total of 134 children aged 6–59 months with severe malnutrition were recruited. Results: Sixty-one (45.5%) had oedematous malnutrition and 73 (54.5%) had severe wasting. Fifty-nine (44.0%) were HIV-infected. The prevalence of bacteraemia was 22%. The predominant organisms isolated were gramnegative enteric bacilli (77%) with Salmonella species and E. coli contributing 67% of the isolates. Hypoglycaemia was significantly associated with bacteraemia (p50.007). Most organisms were resistant to cotrimaxazole (93.3%), ampicillin (76.7%), gentamicin (66.7%) and chloramphenicol (60%). All isolates were sensitive to ceftriaxone. Sensitivity to ciprofloxacin was 97%. There was no strong association between HIV infection and bacteraemia. The relative risk of death in malnourished children with bacteraemia was ten times higher than in those without bacteraemia. Conclusions: Nearly a quarter (22%) of children admitted with severe malnutrition had bacteraemia and gram-negative organisms were the predominant cause. Forty-four per cent were HIV-infected.Most of the bacteria were sensitive to ceftriaxone and ciprofloxacin and resistant to commonly used antibiotics. In the absence of culture and sensitivity, ciprofloxacin or ceftriaxone should be considered as first-line antibiotics for severely malnourished children.
Keywords: Bacteraemia; Severely; Malnourished children; HIV-endemic